Comparison of the Effectiveness of Universal and Targeted Iodine Supplementation in Pregnant Women: A Randomized Controlled Trial - Tugsina Tinna (2020)
© 2020 S. Karger AG, Basel. Objective: To compare the effectiveness of universal and targeted iodine supplementation strategies. Methods: A randomized controlled trial involving low-risk Thai pregnant women was carried out. The participants were categorized into either the study group, in which iodine supplementation was varied based on median urine iodine concentration, or the control group, which received universal supplementation. Urine samples were collected before the start of treatment and at delivery. The primary outcome was iodine status after each supplementation regime. Results: Two hundred and eight women were randomly categorized into 2 groups, 104 control-group participants and 104 study-group participants. Baseline iodine status in both groups was not significantly different. More than half of the pregnant women were classified as having iodine insufficiency. After supplementation, the proportions of iodine insufficiency in the control and study groups (27.9 and 33.3%, respectively; p value = 0.508) and those of excessive level (19.1 and 11.7%, respectively; p value = 0.247) were not significantly different between the 2 groups. However, iodine level above the requirement was statistically significantly higher in the control group (47.1%) compared with the study group (30.0%; p value = 0.048). Conclusions: The 2 strategies, universal and targeted supplementation, have comparable effectiveness in prevention of iodine deficiency, but the evidence suggests that targeted supplementation is better in avoiding over-supplementation.